A Parametric Study on a Subcritical CO2/NH3 Cascade Refrigeration System for Low Temperature Applications - (:unkn) unknown (ASME, 2018)
Adverse effects of synthetic refrigerants on the environment have led to replacing them with natural refrigerants. The common candidates are ammonia, carbon dioxide, and several hydrocarbon compounds and their mixtures. Ammonia has been used mainly in large-scale cooling purposes such as large-scale supermarkets and climatic rooms. However, in such systems, leakage of ammonia may arise severe results on human health and may damage products in the cooled space. Recently, in last decade, a well-known refrigerant, CO2, has gained more attention to be applied in refrigeration systems due to having prominent thermo-physical properties. The performance analysis of a CO2/NH 3 cascade (CAS) system has been theoretically examined in the current study. The detailed performance analysis of the system and optimization of the operating parameters have been studied extensively. In addition, the second-law analysis of the system with both cycles has been performed. Optimum operating conditions of the system are also determined and correlations are developed. Finally, the coefficient of performance (COP) correlations developed by several researchers in literature and those of current study are compared against available experimental COP results. The comparisons showed that the proposed correlations can be utilized for the accurate prediction of the COP of a cascade CO2/NH3 system within the studied range of operating conditions.
Keywords: carbon dioxide; cascade system; optimization; ammonia; exergy; CARBON-DIOXIDE; CO2